2014
DOI: 10.11646/zootaxa.3764.5.3
|View full text |Cite
|
Sign up to set email alerts
|

<p class="HeadingRunIn"><strong>Three new species of the genus <em>Paraleucilla</em> Dendy, 1892 (Porifera, Calcarea) from the coast of Bahia State, Northeastern Brazil</strong></p>

Abstract: Three new species of calcareous sponges from the coast of Bahia State, NE Brazil are described. All of them belong to the genus Paraleucilla (Calcaronea, Leucosolenida, Amphoriscidae): P. solangeae sp. nov., P. oca sp. nov., and P. incomposita sp. nov. The number of species recorded from the Bahia coast has thus increased from 10 to 13. Including these new species, there are now 50 calcareous sponge species known from the entire Brazilian coast. Paraleucilla is now composed of 11 species, six of them occurring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
(7 reference statements)
1
8
0
1
Order By: Relevance
“…Our findings are in agreement with the issues raised by Cavalcanti et al. (), which suggested that thin fragments of the sponge (especially near the osculum) should be avoided in preparing skeleton slides used for taxonomic identification of species of Paraleucilla . It is possible that thin‐walled individuals of Paraleucilla were previously (mistakenly) considered as Leucilla .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our findings are in agreement with the issues raised by Cavalcanti et al. (), which suggested that thin fragments of the sponge (especially near the osculum) should be avoided in preparing skeleton slides used for taxonomic identification of species of Paraleucilla . It is possible that thin‐walled individuals of Paraleucilla were previously (mistakenly) considered as Leucilla .…”
Section: Discussionsupporting
confidence: 93%
“…Recently, Cavalcanti et al. () highlighted that the presence of the DZ was variable among specimens of Paraleucilla solangeae Cavalcanti, Menegola, & Lanna and P. oca Cavalcanti, Menegola, & Lanna . Such variability was likewise observed in other species— P. magna (Klautau et al.…”
mentioning
confidence: 90%
See 3 more Smart Citations